Proenkephalin A 119-159 in kidney transplantation: a novel biomarker for superior tracking of graft function trajectories - Benning, Louise; Reineke, Marvin; Rodrigues, Camila Eleuterio; Kälble, Florian; Speer, Claudius; Sommerer, Claudia; Mahler, Christoph; Schmitt, Felix; Mieth, Markus; Zeier, Martin; Michalski, Christoph; Mehrabi, Arianeb; et al. (Transplant international, 2025)
Accurate assessment of graft function trajectories after kidney transplantation is essential for optimizing patient management. Slow graft function (SGF) and delayed graft function (DGF) are associated with impaired recovery, yet current diagnostic tools lack granularity for timely risk stratification. Proenkephalin A 119-159 (penKid) may improve graft function assessment, enhancing risk stratification for SGF, DGF, and associated outcomes. This prospective study evaluated 159 kidney transplant recipients at Heidelberg University Hospital to compare plasma penKid levels with current risk-indicators for poor (functional) graft trajectories. Validation was conducted using an independent transplant cohort from Sydney. Clinical relevance of biomarker-indicated changes in graft function was assessed using multivariable regression models and AUROC analyses. From day one post-transplant, penKid outperformed serum creatinine (SCr) in identifying functional trajectories associated with DGF (AUROC penKid: 0.87 vs. SCr: 0.56) and differentiated SGF from DGF (AUROC penKid: 0.79 vs. SCr: 0.33) up to eight days earlier. PenKid further demonstrated superior granularity in assessing DGF severity and 30-day outcomes. After adjustment for common risk factors, penKid remained the strongest risk stratifier for all tested outcomes. PenKid is a superior biomarker for earlier assessment of graft function trajectories, offering potential to enhance personalized care and clinical trial designs in kidney transplantation.